Hello,
I’m brand to this site and I’m hoping that someone can show me the individual steps that allows the following equation:
t = P*R/S*E-0.6*P
Transpose to make P the subject per the following equation:
P = S*E*t/R+0.6t
Many Thanks,
Rich.
Hello,
I’m brand to this site and I’m hoping that someone can show me the individual steps that allows the following equation:
t = P*R/S*E-0.6*P
Transpose to make P the subject per the following equation:
P = S*E*t/R+0.6t
Many Thanks,
Rich.
I've managed to figure this out by looking at similar posts (Sorry... I did say I was new!)
Anyway, here are the steps to transpose t = P*R/S*E-0.6*P making P the subject:
1. Multiply by (SE-0.6P)
2. Expand t(SE-0.6P)
3. Add +0.6Pt
4. Factorise PR+0.6Pt
5. Divide by R+0.6t
6. Rearrange P to L.H.S
If I've got this wrong, could someone let me know?
If that the case (denominator as you show) then
your equation requires brackets: t = P*R / (S*E-0.6*P) ; understand?
Crossmultiply:
PR = tSE - .6tP
Add .6tP to each side:
PR + .6tP = tSE
Factor left side:
P(R + .6t) = tSE
Divide each side by R + .6t:
P = tSE / (R + .6t) : notice brackets to CLARIFY denominator!
That's it.
Usually with these, you'd be expected to change .6 to 3/5, thus 3t / 5; so:
P = tSE / (R + 3t/5)
P = tSE / [(5R + 3t) / 5]
P = 5tSE / (5R + 3t)
Capish?